Systemic Lupus Erythematosus with Secondary Thrombotic Thrombocytopenic Purpura and Acute Parkinsonism: A Case Report - Pooja Deepak; Memon, Roha Saeed; Tariq, Fizza; Ahmed, Hassan; Shaheen Bhatti (Journal of the Pakistan Medical Association, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease that has certain characteristic features but can also present with misleading signs and symptoms especially when it is of late-onset. Various case reports address its association with thrombotic thrombocytopenic purpura (TTP), however, its association with parkinsonism remains unclear. We present the case of a 58-year-old male who reported with acute-onset parkinsonism along with some gastrointestinal symptoms. Detailed laboratory investigations unmasked the underlying SLE with an overlapping picture of TTP. This unusual presentation in a resource-constrained setting created challenges and subsequent delays in the diagnosis and management of the patient. Despite urgent care, the patient’s age, presence of overlapping conditions, and multi-organ involvement were some of the factors due to which the treatment failed and he could not survive. We report the association of SLE with secondary TTP and parkinsonism.